Redesign UI/IX Aplikasi Si Pandan Ayu Menggunakan Metode Activity Centered Design (ACD) - Anissa, Claudia; Fahrudin, Rifqi; Suwandi, Suwandi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The development of digital technology has encouraged government agencies to provide application-based services that offer convenience, speed, and an optimal user experience. One of the applications used in administrative services for the population in Indramayu Regency is Si Pandan Ayu. However, based on initial findings, this application still faces challenges in terms of user interface (UI) and user experience (UX), such as confusing navigation and inconsistent design, thereby reducing user comfort. This study aims to redesign the UI/UX of the Si Pandan Ayu application using the Activity Centered Design (ACD) method. This method was chosen because it focuses on users' primary activities in completing tasks, resulting in a design that is more relevant to real-world needs. The research stages include data collection through a pretest (interviews and UEQ questionnaires), analysis of user activities, interface redesign, and design evaluation using UEQ in the posttest phase. The results of the study show that of the six dimensions of the UEQ, the following scores were obtained: attractiveness (1.97), clarity (2.10), efficiency (2.35), accuracy (2.35), stimulation (2.35), and novelty (1.90), all of which fall into the excellent category. Based on the average UEQ scores, the redesign of the Si Pandan Ayu application successfully provided an excellent user experience, leading to the conclusion that the ACD method is effective in improving the UI/UX quality of the Si Pandan Ayu application.